2021
DOI: 10.3389/fnins.2021.630278
|View full text |Cite
|
Sign up to set email alerts
|

Brain Structural Network Compensation Is Associated With Cognitive Impairment and Alzheimer’s Disease Pathology

Abstract: BackgroundStructural network alterations in Alzheimer’s disease (AD) are related to worse cognitive impairment. The aim of this study was to quantify the alterations in gray matter associated with impaired cognition and their pathological biomarkers in AD-spectrum patients.MethodsWe extracted gray matter networks from 3D-T1 magnetic resonance imaging scans, and a graph theory analysis was used to explore alterations in the network metrics in 34 healthy controls, 70 mild cognitive impairment (MCI) patients, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 50 publications
3
11
0
Order By: Relevance
“…Reuter-Lorenz & Cappell, 2008;Sheng et al, 2021;Yao et al, 2010). Our results are in agreement with the aforementioned studies, since they show a significant increase in persistence of information flows at -12-Downloaded from http://direct.mit.edu/netn/article-pdf/doi/10.1162/netn_a_00203/1926667/netn_a_00203.pdf by guest on 14 July 2021…”
supporting
confidence: 92%
“…Reuter-Lorenz & Cappell, 2008;Sheng et al, 2021;Yao et al, 2010). Our results are in agreement with the aforementioned studies, since they show a significant increase in persistence of information flows at -12-Downloaded from http://direct.mit.edu/netn/article-pdf/doi/10.1162/netn_a_00203/1926667/netn_a_00203.pdf by guest on 14 July 2021…”
supporting
confidence: 92%
“…43 In addition to these findings associating cognition and white matter connectivity, Lopez-Soley et al demonstrated in 181 participants that structural brain connectivity is associated with traditional proxy variables for reserve, as measured by a cognitive reserve questionnaire. 44 Together, these findings suggest that interventions aimed at increasing neural connections through brain-stimulating activities, education, and lifelong learning might provide an opportunity for improved resilience 1 .…”
Section: Structural Brain Connectivity and The Reserve Hypothesismentioning
confidence: 98%
“…A recent study using graph theory methods demonstrated that distinct changes in functional connectivity at the global and local network levels were associated with different NPS clusters in patients with AD ( Chang et al, 2020 ). Moreover, another recent study reported that alterations in structural network measures in AD-spectrum patients were associated with impaired memory function and pathological biomarkers of AD ( Sheng et al, 2021 ). Structural covariance network analysis using graph theory methods may offer novel insights into the neural mechanisms underlying MBI at the network level.…”
Section: Introductionmentioning
confidence: 99%